Comparative Study on Impact Assessment of Dead Fish on the Quality Parameters of Fresh and Sea Water - Waghela, Trisha; Bhatt, Vandita; Dariwala, Ammar; Saroj, Dineshkumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Water is vital for ecosystems, supporting biodiversity and sustaining life. Changes in water quality can affect the ecosystem’s animal inhabitants. Decomposition of fish carcasses can lead to deterioration in water quality, posing risk to aquatic animals. This investigation was aimed evaluate the impact of fish carcass on freshwater and seawater quality, by analysing physical and chemical parameters, temperature, salinity, density, pH, Total Dissolved Solids (TDS) and Dissolved Oxygen (DO). Water quality is characterised by physical, chemical, and biological attributes and could be assessed by analysing several parameters such as pH, Temperature, Salinity, DO, and TDS. It was observed that the temperature of freshwater to be 29°C and sea water to be 27°C. There was a decline in density, Dissolved Oxygen, Total Dissolved Solids and pH in both seawater and freshwater, after introducing fish carcass, over the period of three weeks. This study summarizes natural calamities, anthropogenic activities and varied pollution in aquatic environments leading to death of large numbers of aquatic animals which may cause deterioration of water quality and depletion of aquatic biota.